Policy Implementation of Regional Public Service Board (BLUD) in Regional General Hospital of Sidoarjo Regency - Erin Hardiyanti (Jurnal Administrasi Publik, 2013)
Abstract:Policy Implementation of Regional Public Service Board (BLUD) in Regional General Hospital of Sidoarjo Regency. Hospital as one of the types of Public Service Board is the main of the development of public health. Regional General Hospital of Sidoarjo Regency is Local Government Affair Unit that has been implementing Financial Management Pattern of Regional Public Service Board (PPK-BLUD) since January 1, 2009 based on Regent Decree Number 188/1229/404.1.1.2/2008. Hence Regional Public Service Board Sidoarjo Regency is expected to improve the quality of service, efficiency and giving accessibility good enough to the society with providing services such as providing goods and/or services sold without prioritising seeking and based on efficiency principle and productivity. The purpose of this study is how the implementation, result and the constraints faced. This study used method of research that use are qualitative research combined with descriptive approach and tend to use SWOT analysis. The results of this study are BLUD policy implementation results are quite good but there are still many things to be improved and upgraded. The suggestion given are doing improve the marketing of a superior product, need for monitoring and evaluation of employee performance estimation gradually. Keywords: Policy Implementation, Regional Public Service Board